Enhancing environmental security in Central Asia: the role of NATO - Kuzembayeva, A. B. (International relations and international law Journal, 2016)
This article considers NATO’s role in addressing security challenges in Central Asia emanating from the environment that can ultimately lead to disasters, regional tensions and violence. Today NATO and its member-states are significant partners of the whole Central Asian region in general. A number of projects funded under the NATO Science for Peace and Security programme in Central Asia are looking at ways to address ecological problems.